IDENTIFIKASI RENSTRA KAPANEWON BANGUNTAPANRENSTRA KAPANEWON BANGUNTAPAN 2021-2026 - Alfianti, Reni; Jenita, Anjela Yessika; Edot, Florentino Elton Prayoga; Tengko, Yohanes Rivaldo (MAJU : Indonesian Journal of Community Empowerment, 2024)
The Strategic Plan (Renstra) for 2021-2026 Kapanewon Banguntapan is a planning document that aims to describe development directions and strategies for a five-year period in the region. This Strategic Plan was prepared by involving the participation of the community, government and relevant stakeholders for sustainable, inclusive development , and competitiveness. The 2021-2026 Regional Apparatus Strategic Plan was prepared in order to follow up on the 2021-2026 Bantul Regency RPJMD. The Kapanewon Banguntapan Strategic Plan for 2021-2026 is guided by the 2021-2026 Bantul Regency RPJMD and refers to the 2017-2022 DIY RPJMD and considers a number of related documents, namely the 2021-2024 KLHS of the RPJMD, the 2010-2030 RTRW of Bantul Regency.